Dengue Control Model, Abate Sowing and Larvitrap Installation in Dengue Endemic Areas of Kupang City - Kristina, R. H.; Theodolfi, Ragu; Sila, Oktofianus (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
The bite of the Aedes sp mosquito causes nearly 0 million people to be infected with the dengue virus annually, one of areas declared as an endemic area is East Nusa Tenggara Province. 5669 cases and 58 deaths due to dengue hemorrhagic fever (DHF) were found in East Nusa Tenggara Province in 2020 (CFR 1.02%). Highly influential external factors include the availability of clean water, the crisis of drinking water and clean water, and poor condition of water container that do not meet the requirements. This study aims to manage Larvitrap installation movement and abatezation of the water containers in the community/households in Kupang City. This was a observational study with survey design regarding the installation of Larvitrap tool. The density of mosquito larvae was measured based on the House Index (HI), Container Index (CI), and Breteau index (BI). 383 families were involved as the study samples who were selected using the accidental sampling technique. The results showed that there were 866 units of water resevoir (47.8%). Fatululi Village had the highest percentage of indoor water container by 15.7% (140 units), and Oesapa Village had the highest percentage of outdoor water container by 15.5% (143 units). The highest percentage of positive indoor water container was found in TDM and Kelapa Lima by 30.4%, while the highest percentage of positive outdoor water container was found in TDM village by 48.4%. Aedes aegypti larvae and Aedes albopictus larvae were identified in the indoor and outdoor water containers in TDM Village, while that were only aedes aegypti larvae found in six other villages. The positive larvitrap larvae found in Oebufu Village was 15%, 10% was found in Oesapa Village, while there were no larvae found in 5 other villages. The flick density index obtained the highest House Index (HI) in Kelapa Lima village by 58.33%, the highest Container Index (CI) was found in TDM village by 44.03% and the highest Breteau Index (BI) was found in TDM village by 218.75%. It can be concluded that it is necessary to conduct education on mosquito larvae control that involves active community participation and supervision towards weekly draining of community water containers. In addition, abate sprinkling and dengue vector control activities should be carried out simultaneously throughout Kupang City at the beginning of the rainy season, at the peak of case incidence and at the end of the rainy season.